Regionalisation of the Republic of Slovenia - Stane Vlaj (Central European Public Administration Review)
The paper critically examines the planned introduction of fourteen regions in the Republic of Slovenia (RS). Regions as a mandatory second level of selfgovernment will be of major importance for the decentralisation of Slovenia, and consequently for the implementation of the principle of subsidiarity as the fundamental principle in arranging relations between the State and sub-national government levels. However, there are some serious disagreements about the size, competences and financing of the regions. An appropriate division of the state territory into regions is the basis for the optimal territorial organisation of material activities as well as for the settlement of population and decentralisation of state functions. Numerous economic, administrative, geographical and other reasons justify the need to divide Slovenia into regions, preferably into six to eight regions. The paper confronts this project with international criteria and standards as well as with some cases of regionalisation in the European Union (EU) and in the Council of Europe (CE) member states. The author recognises that in almost all CE member states, far-reaching reforms of regional authorities have been completed, are in progress or are planned for the years ahead. The CE, preparing a document (recommendation/convention) on regional self-government, respects the sovereignity and freedom of member states to determine their own internal organisation in conformity with the fundamental standards and principles of democracy. The CE also considers that the process of decentralisation and the regional authorities where they exist can facilitate economic growth, sustainable development, quality public services and the strengthening of democracy.